A Quantitative Study on the Consumption of Organic Fruits and Vegetables in Vietnam - Nguyen Ngoc Thuy; Gunjan Saxena; Keshab Bhattarai; Hoang Ha Anh (SAGE Open)
This study explores the key factors that shape Vietnamese consumers' intentions to purchase organic fruits and vegetables, with a particular focus on the role of consumer trust. Analysis of data collected from 330 randomly sampled individuals in Ho Chi Minh City reveals a distinct connection between unsafe food storage and handling practices and heightened consumer caution. As a result, this increased consumer caution has contributed to a rise in the consumption of organic foods identified as ‘rau an toan’ (RAT), meaning safe produce. Structural equation modelling shows that consumers’ intention to buy RAT products is influenced by their product knowledge and, importantly, their trust in both the products and distributors like corner stores. Other significant factors include cost perceptions, feelings of convenience and concerns about health and the environment. The empirical analysis validates the salience of consumer trust in their purchase intentions towards organic products. This finding is supported using regression, pairwise and non-parametric tests, confirmatory factor analysis and structural equation modelling. Overall, this study offers valuable insights for managers on how to cultivate consumer trust and, in turn, enhance their commitment to purchasing organic fruits and vegetables through targeted marketing. In conclusion, initiatives like the RAT scheme are vital for making sustainable and organic food consumption more accessible.